2019
DOI: 10.1370/afm.2470
|View full text |Cite
|
Sign up to set email alerts
|

Capacity to Address Social Needs Affects Primary Care Clinician Burnout

Abstract: PURPOSE Primary care clinicians disproportionately report symptoms of burnout, threatening workforce sustainability and quality of care. Recent surveys report that these symptoms are greater when clinicians perceive fewer clinic resources to address patients' social needs. We undertook this study to better understand the relationship between burnout and clinic capacity to address social needs. METHODS We completed semistructured, in-person interviews and brief surveys with 29 primary care clinicians serving lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 46 publications
(55 reference statements)
0
40
0
1
Order By: Relevance
“…36 Growing accountability demands, information technology changes, intractable social inequities, resource cutbacks, shrinking autonomy, and time pressure collectively create a sense of disempowerment, reducing the perceived quality of work-life. 36 , 37 , 38 , 39 , 40 , 41 Clinician distress is linked to greater patient dissatisfaction and mistrust plus lower adherence to treatment. 42 It interferes with the capacity to provide empathetic patient care, 43 whereas well-being enhances empathy.…”
mentioning
confidence: 99%
“…36 Growing accountability demands, information technology changes, intractable social inequities, resource cutbacks, shrinking autonomy, and time pressure collectively create a sense of disempowerment, reducing the perceived quality of work-life. 36 , 37 , 38 , 39 , 40 , 41 Clinician distress is linked to greater patient dissatisfaction and mistrust plus lower adherence to treatment. 42 It interferes with the capacity to provide empathetic patient care, 43 whereas well-being enhances empathy.…”
mentioning
confidence: 99%
“…A recent study of physician burnout related to addressing social needs found that clinic-level resources were necessary but not sufficient to address burnout. 20 Meanwhile, another recent study on the capacity of community-based organizations (CBO) to absorb health system referrals concluded that a lack of consideration of CBO capacity undermines the success of clinical and social care integration. 21 These studies together with the current study strongly indicate that the limitations of clinics to provide social needs-targeted care independent of adequately resourced community partners and strong collaboration should be given more attention.…”
Section: Discussionmentioning
confidence: 99%
“…33 The capacity or incapacity to address patients' social needs has been shown to affect primary care physician burnout. 34 Workers in other fields might protest the corruption of their profession's ethical standards by outside forces, but the virtue animating medical ethics precludes many forms of resistance. In this way, the virtuous nature of medical professionalism becomes a force that traps health care workers in clinical environments that undermine their ethical goals, exposes them to psychological injury, and precludes them from deploying methods like strikes or protests to fight for change.…”
Section: Duty To Provide Care As a Substitute For Clinical Empathymentioning
confidence: 99%